(untitled) (Indian Journal of Nematology, 2024)
A study was conducted to evaluate the nematicidal potential of neem and Bacillus thuringiensis in controlling M. incognita. 5% neem leaf extract (NLE) @ 10ml/seedling, 10% neem seed extract (NSE) @ 10ml/seedling, 1.1X 109 CFU/ml Bt formulations alone @ 10ml/seedling and neem+Bt in combination in the ratio1:1 and 2.5% carbofuran 3-G @ 10ml/seedling to control M. incognita infesting tomato plants. Bare-root-dip treatment with NSE was effective and caused 97.3% and 120.3% significant increase (p<0.05) in total plant length and total plant weight respectively as compared to the inoculated control. The study indicated that carbofuran 3-G and WCS+NSE used as bare-root-dip treatment caused significant reduction in number of galls/root system by 75.5% and 42.1% as compared to the inoculated control. The bare-root-dip treatment with carbofuran 3-G, WCS+NLE, CPR+NLE and CPR were effective and caused reduction in number of egg masses/gall by 70%, 49%, 48%, 41%, respectively as compared to the inoculated control. The efficacy of carbofuran 3-G, WCS+NLE, CPR, WCS+NSE as bare-root-dip treatment in reducing number of J2/1g root i.e. 86.8%, 68.9%, 68.4% and 67.3% respectively as compared to the inoculated control. Bare-root-dip treatment with WCS+NSE was effective and caused 63.6% reduction in number of males/250g soil as compared to the inoculated control.